ANALYSIS OF THE USE OF MACROMEDIA FLASH BASED LEARNING MEDIA TO INCREASE THE EFFECTIVENESS OF STUDENT LEARNING AT MTS NEGERI 2 SERANG CITY - Trisnawati, Ayu; Umalihayati, Umalihayati; Tabrani, Mohamad Bayi (Cakrawala Pedagogik, 2025)
This proposition is entitled Investigation of the Utilize of Macromedia Flash-Based Learning Media to Extend the Adequacy of Understudy Learning at MTS Negeri 2 Serang City. This investigate employments a subjective strategy pointed at analyzing how successfully understudies learn utilizing Macromedia Flash-based learning media. The information collection strategy in this investigate employments an unstructured interview technique, which could be a free meet where the analyst does not utilize an meet direct that has been arranged efficiently and totally for information collection. The comes about of information collection by conducting tests and interviews in course VIII B with a add up to of 5 understudies as respondents at MTS Negeri 2 Serang City have demonstrated that the adequacy of learning utilizing Macromedia Flash-based learning media can be connected at school. It can be concluded that understudies some time recently utilizing learning media discover it troublesome to get it the fabric displayed. , after utilizing Macromedia Streak learning media understudies ended up more understanding of the fabric, center on learning, curiously to see at, so that the learning handle gets to be successful. Macromedia Streak based learning media can be connected in schools and can increment viable learning.